A study of the concurrent validity of the Minnesota tests of creative thinking, abbr. form vii, for eighth grade industrial arts students - Duenk, Lester G.; Minnesota Univ., Minneapolis. Dept. of Trade and Industrial Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
The primary objective of this study was to establish the concurrent validity of the Minnesota tests of creative thinking, abbreviated form vii, (mtct vii) by determining the relationship between its scores and creative ability as measured by accumulated teacher ratings of industrial arts projects and investigator-developed tests of creativity. The sample included 129 eighth grade male industrial arts students. The person product movement correlation coefficient was used to estimate the concurrent validity of the mtct vii and to ascertain the relationship between accumulated teacher ratings and the investigator's tests. Multiple regression equations were developed to ascertain which combinations of the variable in the mtct vii would best predict each of the variables in the investigator's test. Some conclusions were--(1) a facility for supplying detail and supporting ideas on a paper and pencil test may be slightly indicative of creative behavior, (2) the facility to generate unusual ideas may be accompanied by the ability to produce useful products, (3) the junior high students with unusual and useful ideas of a figural nature tend to possess more desirable traits of personality than less creative peers, (4) behavioral creativity tends to have little relationship, and symbolic creativity no relationship, to measures of standardized achievement, and (5) both verbal and nonverbal intelligence measures appeared to have a significant but low relationship to specialized performance test measures of figural and behavioral creativity, but insigificant relationships with measures of symbolic creativity. Findings suggest that tne mtct vii may be measuring other factors than are required by students in the creative performance of industrial arts related tasks. (em)
Educational level discussed: Grade 8.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Creativity; Creativity Research; Grade 8.; Industrial Arts; Males; Student Evaluation; Test Validity; Tests; Minnesota Tests of Creative Thinking (Torrance)